Formation and monitoring of secondary X-ray radiation under product processing with electron beam - Pomatsalyuk, R.I.; Shevchenko, V.A.; Titov, D.V.; Tenishev, A.Eh.; Uvarov, V.L.; Zakharchenko, A.A.; Vereshchaka, V.N. (Вопросы атомной науки и техники, 2021)
When conducting an industrial radiation processes at an electron accelerator, a part of the beam energy is transformed into bremsstrahlung radiation. In such a way, the mixed e,X-radiation is formed in the area behind an irradiated object. The intensity of the electron and photon components in the radiation is determined by the energy and power of the primary electron beam, as well as by the parameters of the object and devices located behind it. In paper, the characteristics of the e,X-radiation accompanying the product processing by a scanning electron beam with energy 8…12 MeV at a LU-10 Linac of NSC KIPT are studied. The conditions for obtaining a source of secondary X-rays in the state of electronic equilibrium, as well as its monitoring using an extended free-air ionization chamber are explored. Such an extra-source of radiation can be used for carrying out various non-commercial programs like radiation tests, sanitization of archival materials and cultural heritage objects, etc.